2011
DOI: 10.1088/0256-307x/28/2/020303
|View full text |Cite
|
Sign up to set email alerts
|

Cryptanalysis of Quantum Secure Direct Communication and Authentication Scheme via Bell States

Abstract: The security of the quantum secure direct communication (QSDC) and authentication protocol based on Bell states is analyzed. It is shown that an eavesdropper can invalidate the authentication function, and implement a successful man-in-the-middle attack, where he/she can obtain or even modify the transmitted secret without introducing any error. The particular attack strategy is demonstrated and an improved protocol is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…To design secure quantum cryptographic protocols without this assumption, several authenticated quantum protocols, in which authentication is fulfilled with a shared key and discussion over public classical channels, have been presented [59][60][61][62][63][64][65][66][67]. In 2000, Zeng et al proposed a AQKD protocol with Bell states [59].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To design secure quantum cryptographic protocols without this assumption, several authenticated quantum protocols, in which authentication is fulfilled with a shared key and discussion over public classical channels, have been presented [59][60][61][62][63][64][65][66][67]. In 2000, Zeng et al proposed a AQKD protocol with Bell states [59].…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Liu et al put forward an authenticated QSDC protocol, in which Bell states were used as the quantum information carriers and single photons were used to authenticate communicants [62]. Afterwards, Gao et al showed that this protocol is vulnerable to the MITM attack [63]. In 2013, Lin et al presented a multi-user AQKD protocol with star network topology by utilizing Bell states [64].…”
Section: Introductionmentioning
confidence: 99%
“…Different from them, the quantum cryptography protocols in Refs. [21][22][23][24][25][26][27][28][29][30] do not have the assumption of anthenticated classical channels and need to accomplish the authentication processes first. All of the protocols in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…All of the protocols in Refs. [21][22][23][24][25][26][27][28][29] need to perform the public discussions via the classical channels, which require the receivers to be online. More complicatedly, each of the protocols in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Entanglement is considered to be an important resource for applications of quantum information, such as quantum teleportation [1][2][3][4][5][6][7], quantum secure direct communication [8][9][10][11][12][13][14], remote state preparation [15][16][17][18][19], quantum key distribution [20][21][22][23], and so on. In 2011, Zhang and Cheung [24] proposed the concept of quantum operation sharing (QOS).…”
Section: Introductionmentioning
confidence: 99%